Letter from the Editor - Makinde, Peter Oyewole (WritingThreeSixty, 2025)
It is with immense pleasure and pride that I present to you the second issue of Volume 7 of WritingThreeSixty with the theme: Conflicts of the Wor(l)d: Writing Justice and Peace. This marks a significant milestone in our collective efforts to revive this graduate journal and invite authors from far and wide to captivate us with their academic and creative voices.